Determinan Financial Distress Pemerintah Provinsi di Sumatera - Marina Nalviantry; Rosy Armaini; Riza Wahyudi (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to determine the effect of the alignment of spending, budgetary solvency ratio, and growth ratio on the financial distress of provincial governments in Sumatra. The research employs a quantitative approach. The sampling method used is a saturated sampling technique, which includes all provincial governments in Sumatra. The type of data used is secondary data, obtained through documentation techniques in the form of audited financial statements, namely audit reports from 2019 to 2023. The analytical method applied is panel data regression analysis using the E-Views 12 software. The partial test results show that alignment of spending and the budgetary solvency ratio have a negative and significant effect on financial distress. The simultaneous test results indicate that expenditure alignment, budgetary solvency ratio, and growth ratio collectively have a significant effect on financial distress